THE EFFICACY OF THERAPEUTIC MEASURES IN PATIENTS WITH GENERALIZED PERIODONTITIS ON THE BACKGROUND OF TYPE 1 DIABETES MELLITUS WITH CARDIOMYOPATHY ON SEPARATE PARAMETERS OF THE ORAL LIQUID - T. D. Zabolotnyj; O. I. Kordiyak; R. Y. Shkrebnyuk (Ukrainian Medical Stomatological Academy, 2017)
Abstract. This paper analyzes the efficacy of therapeutic measures in patients with generalized periodontitis and type I diabetes mellitus with cardiomyopathy for changes in the content of concentrations of endothelin-1 and nitrogen metabolites in the oral liquid as the result of use developed own scheme in the main group and control group, where treatment of dental diseases carried out by general accepted method. It is proved that in patients of the main group as a result of treatment were studied in a significant increase in the content of nitrogen metabolites on the background of reducing the concentration of endothelin-1 in the oral liquid compared to the data of control group. The purpose of this work was to study the changes of concentrations of nitrogen metabolites and endothelin-1 in the oral liquid, using own developed treatment and preventive complex in patients with generalized periodontitis on the background of type 1 DM with cardiomyopathy. The material and research methods. The state of periodontal tissues in patients was evaluated by general accepted criteria of dental examination. Diagnosis of periodontal diseases was established according to the classification of M. F. Danilevsky (1994) with additions of I. S. Mashchenko (1997). The diagnosis was specified using periodontal indices. The complex treatment of generalized periodontitis was held in 127 patients with generalized periodontitis on the background of type 1 diabetes mellitus with cardiomyopathy, divided into two groups: main group (82 people) treatment conducted in accordance with own developed schemes. In control group the treatment of generalized periodontitis was performed according to the standard method in accordance with the "Protocols of medical care of Ministry of health of Ukraine on specialty "Therapeutic dentistry". The content of endothelin-1 in the oral fluid was determined by ELISA method using a set of reagents. The content of nitrogen metabolites (NO2 + NO3) in the oral liquid of patients determined according to the standard method. The obtained results were worked out statistically. Results of the research and their discussion. Result of treatment and preventive measures in patients of the main group with GP after 6 months of treatment the content of nitrogen metabolites in the oral liquid has increased for all degrees of severity of generalized periodontitis compared to the values before treatment. In patients of control group with GP after 6 months of treatment, where used traditional therapeutic schemes, the content of nitrogen metabolites in the oral liquid was significantly lower at the initial - I degree of severity of GP relatively to the data before treatment (27.25±1.13 mkmol/l against 30.87±1.12 mkmol/l, p<0.05). Patients of the main group, after 12 months of treatment, noted further decrease of endothelin-1 in the oral liquid relative to the data before treatment: at GP of the initial - I degree of severity on 43.84 %, at GP of II degree of severity on 38.85 % and at GP of III degree of severity on 23.61 %, p<0.01. In the studied of control group after 12 months of treatment the content of endothelin-1 was increased in the oral liquid on 21.43 % more on initial stages of GP, p<0.05. In advanced forms of generalized periodontitis, the level of endothelin-1 was on 22.95 % at GP of II degree of severity, p<0.01 and at GP of III degree of severity on 15.0 % , p<0.05 higher relative to the data before treatment. Conclusions. The study proved the adequacy of the proposed treatment and preventive scheme in patients of the main group, which is confirmed by the improvement of endothelial function of the vessels of the periodontium, which is expressed by increasing the concentrations of nitrogen metabolites on the background of decrease of endothelin-1 in the oral liquid in this group of patients, in the absence of positive dynamics in the control group, where treatment was performed according to standard methods.